DNA Barcoding of Brevibora cheeya from Bumang River, Bangka Island - Eva Lestari; Siti PNIK Almagribi; Lindiatika Lindiatika; Olivia Khanati; Donalista Donalista; Tiara P Anjani; Andri Kurniawan; Ahmad F Syarif; Ardiansyah Kurniawan (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Brevibora cheeya is a cyprinid fish found in Bangka, Belitung, Sumatra, and Kalimantan. Bangka locals call this fish Seluang. This species is often considered Brevibora dorsiocellata due to its similar morphology. Molecular methods that have never been used for this species on Bangka Island can be used to confirm this species. This study uses COI genes (DNA barcoding) to molecularly identify Brevibora cheeya fish from Bangka Island and analyze their relationships. The sampling process was conducted in Bumang River, Bangka Island, in February 2023, and identification was conducted at the University of Bangka Belitung Biological Laboratory. NCBI BLAST and MEGA 11 were used for data analysis. The results showed that fish samples from Bangka Island have intraspecific genetic relatedness to B. cheeya from Belitung Island, Bangka Island, Central Kalimantan, and South Sumatra, with genetic distances ranging from 0% to 0.9%. The closest genetic relationship to Rasbora dorsiocellata is 3.2%. The phylogenetic tree showed a bootstrap value of 91 for relationships with the Bangka, Belitung, and Central Kalimantan databases and a bootstrap value of 95 for relationships with the Bangka and South Sumatra databases.